2020
DOI: 10.5965/1984317816012020193
|View full text |Cite
|
Sign up to set email alerts
|

Inserção e permanência de surdos no mundo do trabalho: estudo exploratório em empresas de um município do centro-oeste goiano

Abstract: O presente estudo abordou a temática da inclusão de pessoas surdas, pretendeu-se, entre outros, identificar quais as dificuldades que os surdos encontram para se inserirem no mundo do trabalho. Realizou-se uma pesquisa bibliográfica sobre esse assunto, e na sequência, uma pesquisa exploratória em seis empresas de um município do Centro-Oeste do estado de Goiás, Brasil, na tentativa de localizar os surdos que estavam empregados, o que não se concretizou. Durante a visita a essas organizações aplicamos um questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
1
0
3
Order By: Relevance
“…PwD need help in their integration, so it is essential that internal communication transmits to the worker in question and his colleagues positive feelings towards the organization, making him understand that inclusion also depends on the actions of each one (Pereira, 2015). Some studies have shown that one of the greatest difficulties for PwD in integrating into the company is associated with communication, which is very confusing and not very flexible (Borges et al, 2020;Scott el at., 2017). Often, these people remain isolated in the workplace, communicating very little with colleagues and employers, which makes it more difficult for them to integrate, ending up being excluded from several functions, even leading to their dismissal or abandonment of the position (Barbra & Mutswanga, 2014;Nota et al, 2013).…”
Section: Interpersonal Communication (Ic)mentioning
confidence: 99%
“…PwD need help in their integration, so it is essential that internal communication transmits to the worker in question and his colleagues positive feelings towards the organization, making him understand that inclusion also depends on the actions of each one (Pereira, 2015). Some studies have shown that one of the greatest difficulties for PwD in integrating into the company is associated with communication, which is very confusing and not very flexible (Borges et al, 2020;Scott el at., 2017). Often, these people remain isolated in the workplace, communicating very little with colleagues and employers, which makes it more difficult for them to integrate, ending up being excluded from several functions, even leading to their dismissal or abandonment of the position (Barbra & Mutswanga, 2014;Nota et al, 2013).…”
Section: Interpersonal Communication (Ic)mentioning
confidence: 99%
“…CorroboraFreitas (2012) argumenta que a lei implementada é uma forma de garantir o acesso do profissional com deficiência ao mercado de trabalho, sendo a principal porta de entrada para oportunidades para estes profissionais. Entretanto,Borges et al (2020) entendem que a lei não é garantia de inserção inclusiva e que haja reconhecimento de seu valor socioeconômico, configurando sua efetividade. Neste contexto, infere-se que as percepções dos…”
unclassified
“…Não se compreende, dessa forma, que esse sujeito possa se comunicar igualmente, utilizando-se de um meio que não seja oral, desde que sejam dadas as condições necessárias para tal. Assim, a escrita da palavra Surdo com letra maiúscula, segundo Borges (2020), refere pertencimento à comunidade surda e que este se comunica através de Libras. Quem se denomina surdo, costumeiramente, faz parte da militância pelos seus direitos, por isso é um termo que possui grande significado.…”
unclassified
“…Historicamente, segundo Borges (2020), os surdos eram tratados com piedade e vistos como pessoas castigadas pelos deuses, sendo considerados também menos inteligentes. Existe ainda o mito, segundo Cromack (2004), de que o surdo seja alguém agressivo, impulsivo, com problemas emocionais, sociais e cognitivos.…”
unclassified